Estudio de factibilidad en técnicas no destructivas para realizar metalografía en campo de componentes estructurales: réplicas metalográficas y microscopio portátil - Salazar Rodríguez, William (2010)
This tesis deals with the feasibility study on two thechniques for the metallography of a component in field analysis differs greatly from that done in a laboratory. component, a Catalytic Oven, to carry out the study of these two techniques: The Met of a portable microscope. In the first chapter, general considerations are mentioned, along with the theoretical aspects as far as regards non-destructive Metallography. The second chapter details the work plan is used for the inspection of a component in the field. It is on the experience gained by inspecting the component, the difficulties presented depending on your configuration, and the areas to be analyzed, at whic is more convenient to use. In the third chapter, we analyze the feasibility of each method, then test them in the analysis of a structural component. In the fourth chapter provides the conclu the use of each method.